Comparison of Depression Signs Before, During and After the Kidney Transplantation in Babol Shahid Beheshti Hospital - Seyed javad Hosseini; Parvin Aziznejadroshan; Mahmoud Hajiahmadi; Soghra Goliroshan; Monireh sadat Mousavi (Golestan University of Medical Sciences, 2018)
Background: Depression is the most common psychological problem in patients with chronic renal failure, which has a negative effect on the outcome of treatment and life quality. The aim of this study was to compare the symptoms of depression in patients referring to the Kidney Transplant Unit of Babol Shahid Beheshti Hospital before transplantation, at discharge and three months after transplantation.       Methods: This descriptive analytical study was conducted on 51 patients receiving renal transplant from November 2014 to February 2015 in Babol Shahid Beheshti Hospital. The non-random sampling method was used. Data were collected using demographic questionnaire and Beck Depression Inventory distributed in three stages. Descriptive and inferential statistics and SPSS18 were used to analyze the data. P=0.05 was considered significant level. Results: Before, at and three months after renal transplantation, 70.6%, 56.9% and 52.9% of the patients had mild to very severe depression, respectively. Mean scores of depression were 19.25 ± 11.99, 14.78 ± 11.45 and 12.82 ± 9.96 before transplantation, at discharge and three months after transplantation, respectively. Paired t-test showed a significant difference between the mean scores of depression before transplantation and at discharge after transplantation (P=0.006), before and three months after kidney transplantation (P = 0.000). There was no significant difference between the time of discharge and three months after transplantation (P=0.135). In addition, no significant difference was found between the scores of depression with gender, marital status, education, occupation and income (p = 0.391). Conclusion: The results indicated a lower incidence of depression in kidney transplanted patients. It is recommended that the patients awaiting transplantation and subsequently their depression status should be intermittently examined and drug or non-drug treatment should be designated for these patients based on the results.